Investigating the Concept of Lata’if in the Naqshbandi Tariqa - Jalali, Abdul Ghafar; Rashid, Abdul Wahab (Farah Research and Scientific Journal, 2025)
The subject of this research is "Examining the Concept of Lataif in the Naqshbandi Order." The concepts under the term Lataif represent the most significant mystical elements, and their activation in light of Sharia guidelines and Sufi principles is, in essence, the only path to attaining the Divine Realm (Lahut) and human perfection. The significance of researching Lataif lies in the fact that they form the fundamental basis of the Naqshbandi Order within the realm of Islamic mysticism.The aim of this study is to define the concept and types of Lataif in the Naqshbandi Order and to highlight their importance in the pursuit of ultimate truth. The findings of this research indicate that Lataif are elements purified from carnal impurities, the phenomenon of anger, and improper inclinations toward disobedience. In the Naqshbandi Sufi tradition, Lataif are classified into two categories: one associated with the Alam al-Amr (the world of divine command) and the other with the Alam al-Khalq (the world of creation). Each category consists of five Lataif, making a total of ten, which are embedded in specific locations within the human body. Regardless of their affiliation with the Alam al-Amr or the Alam al-Khalq, these Lataif serve as the fundamental building blocks in the endeavor to reach and unite with the true spiritual realm. Additionally, the research explores the names of these Lataif and provides justifications derived from Quranic verses and Islamic legal texts, as put forth by the scholars of the Naqshbandi Order. The methodology employed in this study is a descriptive-analytical approach based on library research.